Festival Sebagai Media Komunikasi Dalam Membangun Citra Destinasi Wisata Budaya Di Sumenep - Mohammad Insan Romadhan (Institut Ilmu Sosial dan Manajemen STIAMI, 2019)
Sumenep with its cultural diversity has the potential to become a destination visited by many tourists. This is the duty of the Sumenep regional government to be able to better introduce and build an image as a tourist destination in Indonesia. So that researcher are interested in examining how the Sumenep Tourism and Culture departement build the image Sumenep of a tourist destination. The theory used in this research is management impression theory, Laswell and Aristoteles Communication Model. The research method uses a qualitative approach, with a type of descriptive research and using a case study method. Research informant is head of promotion in the tourism and cultural departement of Sumenep. The data collection technique in this research used interviews, observation and documentation. The result of the research on the process of building the image of the efforts made by showing and displaying the Sumenep cultures, for example kerapan sapi, sapi sonok, tong-tong music, saronen music to presented to the public. So the impression public would perceive as expected. Selection of the festival as a communication channel for the delivery of a message is deemed appropriate to the interests of public. For self presentation strategy is a strategy of self-promotion